Trans-nasal PEG: An alternative approach to conventional PEG in patients with restricted mouth opening - Akash Goel; Pankaj Singh; Muzaffar Rashid Shawl; Vikas Singla (International Journal of Gastrointestinal Intervention, 2025)
Enteral nutrition is crucial and prognostically significant in patients with advanced malignancies. However, in many such patients, limited mouth opening renders conventional percutaneous endoscopic gastrostomy (PEG) tube placement impossible. Available options include a long-term indwelling naso-gastric tube or a surgical feeding jejunostomy. Long-term naso-gastric tube placement is associated with its own complications, and surgical feeding jejunostomy typically requires general anaesthesia, which is challenging in these debilitated patients. We present a trans-nasal PEG tube insertion technique that can be performed under local anaesthesia or mild sedation to ensure adequate enteral nutrition. The intricate steps of this procedure are detailed to raise awareness among endoscopists.